Krizne točke za nastanak štete u vijeku sportaša, posebno s aspekta uloge trenera koji (ne) radi lege artis - Kačer, Hrvoje (Array, 2019)
The legal framework of the coach’s possible damages liability towards the athlete is analysed in this article. Two hypotheses are starting points. The first one is possible responsibility of the athlete due to expert omissions of the coach in the training process. The second is that coaches are not aware of the limits of their liability. It is completely certain that both hypotheses place coaches in grave danger. Namely, it is correct that there is a great number of working coaches who have not satisfied legal regulations and it is even more certain that there are coaches who do not possess minimal legal knowledge. The authors are sure (although it is only exceptionally possible to make such an assumption without specific scientific research) that a very small number of coaches satisfy the legal standard of „ duty of care of a good expert “from the Contracts Act, even where experts with the highest academic and practical tiles and achievements are concerned. This means that the situation with many coaches is really of the utmost concern. In so far as there is no quality education, the picture of a coach training a child surrounded by (and impede work) the police, district attorney, experts, and perhaps a few more people very quickly will soon turn into worrying picture of reality. Unbelievably, will such predictions be looked upon by physicians. It has been shown that the reality very soon was and is, in our opinion, much worse.